Community-based prevention of epidemic Rocky Mountain spotted fever among minority populations in Sonora, Mexico, using a One Health approach. (10th December 2019) - Alvarez-Hernandez, Gerardo; Drexler, Naomi; Paddock, Christopher D; Licona-Enriquez, Jesus D; la Mora, Jesus Delgado-de; Straily, Anne; del Carmen Candia-Plata, Maria; Cruz-Loustaunau, Denica I; Arteaga-Cardenas, Vanessa A
Abstract: Background: Rocky Mountain spotted fever (RMSF) is a significant public health problem in Sonora, Mexico, resulting in thousands of cases and hundreds of deaths. Outbreaks of RMSF are perpetuated by heavy brown dog tick infestations in and around homes. During 2009–2015, there were 61 RMSF cases and 23 deaths in a single community of Sonora (Community A). Methods: An integrated intervention was carried out from March–November 2016 aimed at reducing tick populations with long-acting acaricidal collars on dogs, environmental acaricides applied to peri-domestic areas and RMSF education. Tick levels were measured by inspection of community dogs to monitor efficacy of the intervention. A similar neighborhood (Community B) was selected for comparison and received standard care (acaricide treatment and education). Results: The prevalence of tick-infested dogs in Community A declined from 32.5% to 8.8% (p<0.01). No new cases of RMSF were identified in this area during the subsequent 18 mo. By comparison, the percentage of tick-infested dogs in Community B decreased from 19% to 13.4% (p=0.36) and two cases were reported, including one death. Conclusions: Community-based interventions using an integrated approach to control brown dog ticks can diminish the morbidity and mortality attributable to RMSF.